The importance of shoot morphological plasticity on plant coexistence: a pot experiment. (17th March 2022) - Hermlin, H. K.; Lepik, M.; Zobel, K.
Abstract: Plant morphological plasticity affects species coexistence by enhancing local coexistence. Here, we test the importance of plasticity to light availability for species coexistence. We hypothesise that high average plasticity in a species assemblage promotes coexistence and tested for the effect of differential plasticity on the competitive success of neighbouring species. Sixteen herbaceous species with known morphological plasticity were grown pairwise in 95 combinations in 285 pots. We calculated mean plasticity and difference of plasticity for each pair of species in a pot using previously estimated degree of plasticity in leaf number, leaf length, leaf area and SLA. We then related these to biomass‐based evenness of abundance in a pot and to competitive success of the 16 species. Unexpectedly, average plasticity did not affect biomass production between coexisting species. Instead, large differences in plasticity among two competitive neighbours predicted low diversity (high degree of dominance) in an assemblage. Higher than neighbour plasticity generally predicted competitive superiority in an assemblage. The opposite was true for plasticity of SLA, where species with low plasticity tended to dominate. Unlike earlier field studies, our results show that phenotypic plasticity in various plant traits pose opposite effects to interspecific competition. Subsequently, these effects possibly affect species composition and richness through which plasticity has significant consequences for plant communities and, therefore, should be accounted for in relevant studies in plant ecology. Abstract : Neighbouring species similar in their plasticity result in even communities, while the degree of plasticity in different traits predicts either competitive superiority or competitive inferiority.